Business Strategy Models MSMEs Corn in West Java; An overview of the aspects of entrepreneurial and environmental orientation external - Achyarsyah, Mochamad; Hendrayati, Heny; Syahidah, Rahmy Karimah; Nurdin, Mohammad; Muhammad, Achmad (Politeknik APP Jakarta, 2024)
Indonesia has many corn-producing areas, but the need for corn still cannot be fulfilled because several regions cannot produce corn to the fullest, especially in West Java. Besides that, The Covid-19 pandemic has caused a need for more corn buyers, both from factories and collectors, to absorb corn yields from farmers. This condition indicates that the climate for small and medium business activities in the agricultural sector, especially corn, still needs to be more conducive and optimal. This study aims to analyze the influence of Entrepreneurial Orientation and External Environment on Business Strategy. The data collection results were analyzed using the Pearson correlation method and linear regression analysis. The results of the study show that business strategy is influenced by entrepreneurial orientation and the external environment. Entrepreneurial orientation and the external environment must be honed and continuously improved to impact innovative business strategies' power significantly.